KAJIAN EFEKTIVITAS SUMUR RESAPAN DI KECAMATAN DENPASAR BARAT - Tri Hayatining Pamungkas; Ida Bagus Weda Erlangga; Kadek Budhi Warsana; Putu Doddy Heka Ardana; I Ketut Soriarta (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
West Denpasar District is a densely populated area with 206,958 people. One of the environmental problems that occur is the frequent occurrence of floods due to the increase in residential areas. One way to overcome this is to build infiltration wells to reduce flood risk, reducing flood volume and discharge. The methods used are descriptive and quantitative. The analysis is carried out by describing the conditions of the study site, then continues with mapping analysis, hydrological analysis, infiltration well analysis, and effectiveness analysis. The analysis results stated that the peak discharge of the 50-year-old flood at the study site was 268. 90 m3/sec. Furthermore, the results of the planning analysis of the application of infiltration wells carried out in the West Denpasar District area, which is included in the Badung River Basin, can reduce flood discharge up to 41. 25%, and for flood runoff, volumes up to 51. 38%. Based on these results, it can be interpreted that infiltration wells have a role in reducing the risk of flood disasters in the West Denpasar District.